Frequency response of the noise conversion from relative intensity noise to phase noise in the photodetection of an optical pulse train - Wu, Kan (2013)
The frequency response of the noise conversion from the relative intensity noise (RIN) to the phase noise in the photodetection process of an optical pulse train is characterized with pump modulation method. It is found that the conversion ratio from the RIN to the phase noise is not sensitive to the noise power or the incident optical power, but decreases approximately as 1/f with the increase of noise frequency. A new parameter defined as the RF power difference of the noise spurious peaks is proposed and is shown to provide an easy way to estimate the strength of the RIN-to-phase-noise conversion avoiding the need to measure the exact noise spectra of the RIN and the phase noise.